Documentary trial plays in contemporary American theater - O'Connor, Jacqueline (Theater in the Americas, 2013)
"The development of the documentary trial play in late-twentieth-century American theater From the Chicago Conspiracy Trial and the O. J. Simpson trial to the Clarence Thomas/Anita Hill congressional hearings, legal and legislative proceedings in the latter part of the twentieth-century kept Americans spellbound. Situated on the shifting border between imagination and the law, trial plays edit, arrange, and reproduce court records, media coverage, and first-person interviews, transforming these elements into a performance. In this first book-length critical study of contemporary American documentary theater, Jacqueline O'Connor examines in depth ten such plays, all written and staged since 1970, and considers the role of the genre in re-creating and revising narratives of significant conflicts in contemporary history. Documentary theater, she shows, is a particularly appropriate and widely utilized theatrical form for engaging in debate about tensions between civil rights and institutional power, the inconsistency of justice, and challenges to gender norms. For each of the plays discussed, including The Trial of the Catonsville Nine, Unquestioned Integrity: The Hill/Thomas Hearings, and The Laramie Project, O'Connor provides historical context and a brief production history before considering the trial the play focuses on. Grouping plays historically and thematically, she demonstrates how dramatic representation advances our understanding of the law's power while revealing the complexities that hinder society's pursuit of justice. "--